2017
DOI: 10.1590/0100-3984.2015.0140
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the cirrhotic liver: diagnosis of hepatocellular carcinoma and evaluation of response to treatment – Part 2

Abstract: In the second part of this review, we will describe the ancillary imaging features of hepatocellular carcinoma (HCC) that can be seen on standard magnetic resonance imaging (MRI) protocol, and on novel and emerging protocols such as diffusion weighted imaging and utilization of hepatocyte-specific/hepatobiliary contrast agent. We will also describe the morphologic sub-types of HCC, and give a simplified non-invasive diagnostic algorithm for HCC, followed by a brief description of the liver imaging reporting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…We prospectively analyzed 100 consecutive CT angiography examinations of the abdomen performed at the General Hospital of Fortaleza over a one-year period. The imaging evaluation of the rhino-orbital region has been the object of a series of recent publications in the radiology literature of Brazil 24 - 29 .…”
Section: Discussionmentioning
confidence: 99%
“…We prospectively analyzed 100 consecutive CT angiography examinations of the abdomen performed at the General Hospital of Fortaleza over a one-year period. The imaging evaluation of the rhino-orbital region has been the object of a series of recent publications in the radiology literature of Brazil 24 - 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with dynamic enhanced CT and enhanced MRI of Gd-DTPA, the enhanced MRI of Gd-EOB-DTPA has higher detection sensitivity for the diagnosis of HCC with rich or poor blood supply [ 15 ]. Compared with other imaging methods, Gd-EOB-DTPA-enhanced MRI can significantly improve the detection rate and diagnostic accuracy for early liver cancer [ 26 ]. Although the feasibility of conventional enhanced MRI in the diagnosis of HCC has been widely recognized, the accuracy and sensitivity for the diagnosis of small HCC with a diameter of < 2.0 cm remains inadequate [ 27 ] and fails to fully meet clinical needs.…”
Section: Main Textmentioning
confidence: 99%
“… 9 So, any T2 elongation in at-risk patients should be considered as highly suggestive of a malignancy. 55 Evidence have shown that T2-weighted imaging is particularly valuable together with diffusion-weighted imaging (DWI) for differentiating between small atypical HCCs (<3 cm) and dysplastic nodules, 56 as the presence of mild-moderate T2 hyperintensity or restricted diffusion strongly favors the diagnosis of a malignant nodule in cirrhotic patients, even if the typical feature of the arterial hyperenhancement is still missing. 10 …”
Section: Ancillary Featuresmentioning
confidence: 99%
“…Although it is relatively uncommon (having a sensitivity for HCC of 12–37%), this feature has a high specificity for HCC (68–100%); hence, in a high-risk population, the detection of intralesional fat in a solid hepatic nodule should raise concerns for HCC. 23 , 55 , 89 …”
Section: Ancillary Featuresmentioning
confidence: 99%